GROUP COHESION IMPORTANT FACTOR IN SPORT PERFORMANCE - Sabin, Sopa Ioan; Marcel, Pomohaci (European Scientific Journal, ESJ, 2014)
Group cohesion is becoming more and more important in any activities were performance is the main purpose. In group sports, like in any other performance based activities, high group cohesion is considered to be very helpful, and has led to better performance. The cohesiveness of sports group mostly refers to the strength of bonds between group members, the unity of a group, the feeling of attraction between group members, and the degree to which members concentrate their efforts to achieve group goals. Therefore, from ascertaining that in groups where there are positive relationships of sympathy, friendship and cooperation, the activity is most effective. Thus, we had tried in this study to analyze and develop cohesion in a sport group. The purpose of this study is to know how group cohesion can influence team performance, how positive attraction relationships can lead to better performance and mostly, how we can reintegrate the marginalized members in the group using sport activities. Using the observation method, the survey method and the social metric test, we analyzed the cohesion index of a sport group. In addition, we studied the preferential relationships of election and rejection; and we tried to find ways to reintegrate the marginalized subjects in the social group.